Performance evaluation of concrete using treated recycled aggregates modified with mineral admixtures: Influence of processing. Issue 3 (17th February 2023) - Verma, Abhishek; Velaga, B. S.; Arunachalam, S.
Abstract: In this study, a new hybrid technique called 'soaking in mild acetic acid followed by mechanical grinding' has been introduced to produce treated recycled aggregate (TRA) extracted from construction and demolition (C&D) waste. In this treatment technique, 17.98% of adherent mortar was removed from untreated recycled aggregate (RA). Two different types of mineral admixtures viz: silica fume (SF) and portland pozzolana cement (PPC) were used to improve the microstructure and to strengthen the interfacial transition zone (ITZ) of RA. In this work, 100% natural aggregate (NA) was replaced with four different types of aggregates viz: TRAs (TRA(SF), TRA(PPC), TRA) and RA at four different water-cement (w/c) ratios (i.e. 0.45, 0.55, 0.65 and 0.75). Fresh, hardened, and durable concrete properties were like slump, compressive strength, tensile strength, flexural strength, elastic modulus, sorptivity, chloride ion permeability, surface resistivity, etc.; microstructure was analyzed and compared with test results of natural aggregate concrete (NAC). Experimental results indicate that concrete made with TRAs showed better results than concrete made with untreated RA. Based on test results, NA substitution with TRAs is possible with reduced compressive strength for lower to medium strength concretes if designed appropriately.